A STUDY ON REQUESTING SPEECH ACTS IN DREAMWORKS PICTURES’ FILM NEED FOR SPEED - Firdhaus, Muhammad; Rianugraha, Yose (Conscientia - Journal on Language, Literature, and Culture, 2023)
One of the branches of linguistics is Pragmatics. In pragmatics we can learn about speech acts. This research analyzed requesting of speech act in the Need For Speed movie by DreamWorks Pictures. The writers use qualitative methods of description and use theories from Trosborg’s and supported by other theories to find the speech act of request expressed by each character in the Need For Speed movie. The scope of this study is focused on the strategies of requests found in the script of the Need For Speed movie. The purpose of this research is to reveal requesting of speech act along with the strategies of requesting by each character in the Need For Speed movie. The results showed that there are sixteen strategies of requests that have been classified into four imperatives, eight statements of needed and wishes, three statements of hearer and demand, and one obligation or willingness.